Medical And Non-Medical Solid Waste Management System at The Regional General Hospital of Kediri Regency - Indasah; Juliandri, Lukius; Nurul Puspa (Journal of Community Engagement in Health, 2025)
The development of hospitals in Indonesia has been increasing rapidly in recent years. Along with the increasing number of hospitals each year, the amount of medical waste produced also rises. If medical waste is not managed properly, this condition will increase the potential for hospital waste to pollute the environment, spread diseases, and cause occupational accident. The solid waste management process at RSKK includes sorting and containment, transportation, storage, and management. This study aims to identify the solid waste management system, both medical and non-medical, at Kediri General Hospital. The methods used are the fishbone diagram, Urgency, Seriousness, Growth (USG) method, and analyzed by Strength, Weakness, Opportunity, Threat (SWOT). Based on the assessment results, the problem determination related to the medical and non-medical solid waste management system at Kediri General Hospital was obtained. Proposed solutions to address these issues include maximizing storage in the non-medical waste Temporary Storage Site (TPS) to be stored or contained separately according to the type, as well as the need for a waste bank for non-medical solid waste management, providing training for management officers and operators to obtain a competency certificate for hazardous and toxic waste management, and increasing human resources for hospital waste management. This research specifically examines strategies for medical and non-medical solid waste management systems and identifies solutions to these problems.